Detection of Trypanosoma vivax in tissues of experimentally infected goats: what is the role of adipose tissue in the life cycle of this protozoon? - Machado, Rosangela Zacarias [UNESP]; Castilho Neto, Kayo José Garcia de Almeida [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Machado, Gisele Fabrino [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP]; Jussiani, Giulia [UNESP]; Silva, Thiago Merighi Vieira da [UNESP]; Gimenes, Lindsay Unno [UNESP]; Jackson, Andrew; Wright, Gavin; Teixeira, Marta Maria Geraldes (FapUNIFESP (SciELO), 2021)
Trypanosomiasis, caused by Trypanosoma vivax, is responsible for great economic losses among livestock in Africa and South America. During the life cycle of these parasites, they may present different morphological, metabolic and physiological characteristics depending on the interactions that are encountered at each point of their life cycle. Although T. vivax is frequently reported in the circulation of its mammalian hosts, it has the ability to migrate to the tissues of these individuals. However, this characteristic is poorly understood. In this context, we aimed to investigate the presence of T. vivax and the changes caused in different tissues of experimentally infected goats. Despite the animals were not perfused before tissues collection, using different approaches, we demonstrated its presence in different samples, including in the adipose tissue and skin of infected animals. In addition, a mononuclear inflammatory reaction, mostly characterized by an infiltrate of lymphocytes, plasma cells and macrophages were observed. The results highlight the possibility that, like other trypanosomatids, T. vivax may use these tissues during its life cycle. Future studies aiming to elucidate the length of time for which T. vivax remains active in these sites, and whether it uses these sites as a refuge from trypanocidal drugs, and whether it is capable of recolonizing the blood circulation, are much needed.